SPECIALIZATION OF AGRICULTURAL LAND IN THE ARAL SEA REGION: CHALLENGES AND IMPLICATIONS - Kdirbayeva Gulan Utebayevna (Academia Science Repository, 2023)
This article explores the issues surrounding the specialization of agricultural land in the Karakalpakstan Aral strip. The region, heavily affected by the ecological disaster of the shrinking Aral Sea, has witnessed significant changes in its agricultural practices. The article examines the impacts of land specialization on the local economy, environment, and social fabric. It discusses the advantages and challenges associated with specialized agriculture, such as increased productivity and market competitiveness versus the potential risks of monoculture, land degradation, and loss of biodiversity. The article concludes by highlighting the need for sustainable land management strategies that promote diversification, ecological resilience, and community well-being in the context of the Karakalpakstan Aral strip.